Segmentation of texture images using fractal transformations - Kasparis, Takis; Pongratananukul, Nattorn (My University, 2000)
This paper presents an approach to textured image segmentation based on a combination of fractal features. The traditional fractal dimension obtained from the original and pre-processed images and is combined with fractal transformation coefficients. The latter are extracted using methodologies from image compression using Iterated Function Systems (IFS). Experiments have shown that coefficients used in IFS for image reconstruction can also be used as segmentation and classification features. Experimental results with various natural texture mosaics will be presented.
Keywords: Computational geometry; Computer simulation; Fractals; Image reconstruction; Mandelbrot set